The Practice of Piety : Puritan Devotional Disciplines in Seventeenth-Century New England - Hambrick-Stowe, Charles E. (Book collections on Project MUSE., 2019)
A moving and vivid account of what it meant to be a Puritan, this account draws on diaries, spiritual biographies, and devotional manuals to explore the daily and weekly ritual and discipline. The devotional movement was at the heart of Puritanism, and the spiritual pilgrimage was the soul's progress from birth to death to rebirth and eternal glory. Puritan worship brought together college student and illiterate farmer, giving coherence to the community.